Dualisme Rezim Hukum Pegawai Tetap Non-PNS Perguruan Tinggi Negeri Badan Hukum yang Berkedudukan Sebagai Pejabat Negara - Fairuz Zahirah Zihni Hamdan; Tony Hanoraga (Notaire, 2026)
The appointment of permanent non-civil servant staff from State Universities with Legal Entity Status (PTNBH) as State Officials at Non-Ministerial Government Agencies (LPNK) triggers complexities of a dual legal regime and potential conflicts of interest. This research aims to analyse the legal standing of such staff serving as state officials, and to formulate legal resolutions consequent to this dual regime and potential conflict of interest. Utilising normative legal research alongside conceptual and statutory approaches, this study demonstrates that permanent non-civil servant staff at a PTNBH are initially workers bound by an Indefinite Term Employment Agreement (PKWTT) under the private employment law regime. Upon appointment to LPNK leadership, their legal standing transforms into that of a state official, entering the public administrative law regime. Such transformation highlights the urgency of temporary suspension to prevent conflicts of interest between executing state duties and fulfilling academic responsibilities at the PTNBH. This deactivation further functions as a preventive measure against State Budget (APBN) inefficiency due to dual remuneration if suspension is omitted. Temporary suspensions must be predicated upon internal PTNBH regulations. Should internal regulations be absent, a legal lacuna arises when temporary suspension must be executed. Responding to this administrative exigency and legal lacuna, university leadership may draft a Bipartite Agreement via a PKWTT Addendum as the legal basis for suspending contract-bound staff, or append a Letter of Temporary Waiver of Rights complementing the Suspension Decree for staff appointed solely via a Rector's Decree upon acquiring permanent non-civil servant status.